Biocatalytic CO2 fixation initiates selective oxidative cracking of 1-naphthol under ambient conditions. Issue 12 (7th June 2022) - Ren, Pengju; Tan, Zijian; Zhou, Yingying; Tang, Hongzhi; Xu, Ping; Liu, Haifeng; Zhu, Leilei
Abstract : CO2 fixation initiates cracking: the enzymatic ortho-carboxylation activates the singly hydroxylated aromatic ring of naphthalene for the following selective cracking catalyzed by dioxygenase in a cofactor-free one-pot cascade reaction. Abstract : The use of carbon dioxide as the C1 source for the production of value-added chemicals has attracted great interest in both academia and industry. Here we report the potential application of CO2 fixation in initiating mild cracking of naphthalene derivatives, the main aromatic compounds in light cycle oil. As a proof-of-concept, 1-naphthol is converted into 2′-carboxybenzyl-pyruvic acid with 100% atom economy and 78.5% overall yield at room temperature in a one-pot enzymatic cascade reaction, which is initiated by carboxylation using atmospheric CO2 followed by oxidative cleavage in air. Our results suggest that cofactor-free carboxylation coupled with an oxygenation reaction is a promising approach for the economically feasible upgrading of light cycle oil, a low quality feedstock for diesel fuel production, to monoaromatic petrochemicals under ambient conditions.